Hubungan Fiqih dengan Ushul Fiqih serta Manfaat Mempelajarinya - Nasir, Muhamad Nasirudin; Yusuf, Aldy Zahasfana; Rofiqul, Ahmad Rofiqul A'la (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
In the basic concept of understanding ushul fiqh, studying the meaning, object of study, objectives, functions and sources of adoption of Islamic law. The methods and approaches studied in Ushul Fiqh provide a framework for fiqh experts in interpreting and deriving laws from these sources. Meanwhile, Fiqh applies the principles and methodology learned in Ushul Fiqh in implementing Islamic laws in various aspects of life. Ushul Fiqh and Fiqh have a close relationship. Ushul Fiqh provides the theoretical foundation, methodology and principles of interpretation, while Fiqh provides practical implementation in issuing Islamic laws. This relationship plays an important role in understanding, establishing, and implementing Islamic laws in the daily lives of Muslims.